2005
DOI: 10.1590/s0100-879x2005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular actions of angiotensin-(1-7)

Abstract: Angiotensin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 56 publications
5
114
1
1
Order By: Relevance
“…It has been shown, in rats and humans that ACE inhibitors can decrease body weight (34 -36). Furthermore, many studies have shown that Ang-(1-7) can counter-regulate Ang II actions and participate in the ACE inhibitor effects (37,38). Our data showing an increased fat mass in Mas-KO mice suggest that the Ang-(1-7)/Mas axis is crucial in the control of fat accumulation and lipolysis.…”
Section: Discussionsupporting
confidence: 49%
“…It has been shown, in rats and humans that ACE inhibitors can decrease body weight (34 -36). Furthermore, many studies have shown that Ang-(1-7) can counter-regulate Ang II actions and participate in the ACE inhibitor effects (37,38). Our data showing an increased fat mass in Mas-KO mice suggest that the Ang-(1-7)/Mas axis is crucial in the control of fat accumulation and lipolysis.…”
Section: Discussionsupporting
confidence: 49%
“…Ang(1-7) has been shown to cause vasorelaxation in multiple vascular beds [7][8][9][10][11] through the release of vasodilator prostaglandins, nitric oxide and endothelial-derived relaxing factor. 7,12 With regard to the heart, Ang(1-7) can decrease hypertrophy and fibrosis induced by Ang II. 13 Additionally, ACE2 overexpression in the heart has been shown to protect against cardiac damage induced by Ang II or seen in spontaneously hypertensive rats (SHR).…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 has a high affinity for Ang II to form Ang (1-7), which is also formed by the action of ACE on Ang (1-9). 47,48 Possibly the degradation of Ang I can also result from the action of ACE, due to high levels of activity and protein expression found in this study. As described in the literature, ACE 3,4 and/or tonin 13,21,22 pathways may contribute to the low levels of Ang I.…”
Section: Discussionmentioning
confidence: 70%